The melancholic unnamable: Kristeva and the question of subjectivity in Beckett’s The Unnamable - Kamran Ahmadgoli; Nima Taheri (Teaching English Language, 2014)
Thestudy of subjectivity is especially relevant to psychoanalysis since it avoids socialand political qualifications, and focuses on the structure of the narrativevoice. In this respect, Kristeva’s innovative psychoanalytic notion ofmelancholia, as an incapacitating desire not to let go of the Real m/Other, isapplied in the present article to the ontological impasse of the impoverished figureof Samuel Beckett’s The Unnamable (1958,2003). It can be formulated as an ontological shade lingering within thisprecarious state, cast between life and death, and seeking the unnamable Thingwhich would be the real silence, corresponding at last to a voice of his own, thevoice of voicelessness. Kristeva’s solution for this suicidal predicament,adopted in this study, is an aesthetic resort to the poetical dimension oflanguage retrieving traces of the dead m/Other, and the fundamental function ofdenegation at once affirming and rejecting the m/Other. A semiotic analysis of The Unnamable, considering, amongothers, the pronouns and commas will reveal a latent materiality in the text:formal derangement. We propose that, through the metaphorical dialectic of thesemiotic process and the symbolic representation, the unnamable-reader achieves,on a trans-symbolic scale, a melancholy sublime, the jouissance of formlessnessbefore the unpresentable presence of the m/Other. This will yield ourinterpretation of the unnamable as an idealized subject-in-process (sujet-en-process) in terms of a pureflow of words: novel as mere ‘going on.’ Therefore, the study presented here isan attempt to bring together the Beckettian destitution of the novel andKristeva’s black sun through a jouissant dynamismof signs undermining the laws of the very language in which they arecontinuously generated.